Pengaruh Efektivitas Penerapan Insentif, dan Motivasi terhadap Kinerja Karyawan PT. PLN (Persero) Rayon Kuta - Desiana Katoda (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
Employee performance is one of the important elements that determine the success of an organization, especially in companies engaged in public services such as PT. PLN (Persero). This study was conducted to examine the effectiveness of providing incentives and motivation in improving employee performance at PT. PLN (Persero) Rayon Kuta, with the aim of providing strategic recommendations for management in formulating more optimal human resource management policies. The research method used is a quantitative approach with a survey technique, where data were collected by distributing questionnaires to 40 employees who were respondents. Data analysis was carried out using a regression test to determine the effect of each variable on employee performance. The results of the study revealed that incentives and motivation have a positive and significant effect on improving performance. Of the two variables, incentives provide a more dominant contribution to employee performance with a regression coefficient value of β = 0.576, while motivation provides a lower influence with a value of β = 0.241. In addition, the F-count value of 24.641 indicates a strong simultaneous influence of incentives and motivation on employee performance. These findings confirm that a well-designed incentive system, coupled with efforts to increase work motivation, can be an effective strategy for boosting employee productivity and performance. Therefore, management needs to prioritize fair, transparent, and target-oriented incentive policies, while also addressing intrinsic motivation to maintain sustainable performance.